Ostrich as a Promising Commodity: Classification and Bioloical Superiority of Ostrich (Struthio Camelus) - Pius P Ketaren (Indonesian Center for Animal Research and Development, 1999)
Ostrich (Struthio camelus) is a flightless and biggest bird, classified as Aves and originated from Africa . Although has been domesticated and fanned for more than 100 years, it is generally agreed that information on ostrich fanning technology is limited not only in Indonesia but also in overseas . Superiorities of ostrich over other birds are: (1) mature ostrich weight between 150-200 kg and 2-3 m tall, (2) live weight of 100 kg can be achieved before 12 months old, (3) digesting high crude fibre diet, (4) digesting feed efficiently, (5) may live up to 70 years old and (6) low fat, cholesterol and energy content of meat. The main source of income in a commercial ostrich farm in South Africa were from leather, meat and feather sales. Research on ostrich in Indonesia has to be well planned to obtain appropriate fanning and after harvest technologies suitable for the Indonesian environment as ostrich fanning had been just introduced in 1996. Key words: Ostrich, biological superiority, main products, income